1968
DOI: 10.1042/bj1060811
|View full text |Cite
|
Sign up to set email alerts
|

Uptake, distribution and binding of beryllium to organelles of the rat liver cell

Abstract: 1. Male rats were injected intravenously with amounts ranging from 0.08 to 111.0mumoles of [(7)Be]beryllium sulphate/kg. body wt. The distribution in the rat and the subcellular distribution of beryllium in the liver were determined. 2. Within the entire dose range a higher specific activity of beryllium was present in a mitochondrial fraction containing the lysosomes. Purification of this fraction confirmed that beryllium is taken up by lysosomes. 3. With doses approaching the LD(50), beryllium was also found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1969
1969
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Activities below the detection limit of 0.1 Bq/kg d.w. were found only four times in autumn periods 2009e2011. These results were expected due to several facts: i) beryllium incorporates into cell membranes due to its biochemical behavior (Witschi and Aldridge, 1968); ii) the phytoplantkon bio-production in northern hemisphere (mussel food source) is higher in spring compared to the autumn season (Wildgust et al, 1998); iii) 7 Be (T 1/2 ¼ 53.4 days) enters the marine environment almost exclusively by atmospheric precipitation and/ or surface and groundwater discharges resulting in its considerably lower input to the marine environment during dry summer and early autumn seasons. Seasonal variations of 7 Be activities in mussels' soft tissue were also comparable to those measured for 210 Po (Ro zmari c et al, 2013) due to similar 7 Be and 210 Po bioaccumulation processes and their input to the marine environment.…”
Section: Resultsmentioning
confidence: 56%
“…Activities below the detection limit of 0.1 Bq/kg d.w. were found only four times in autumn periods 2009e2011. These results were expected due to several facts: i) beryllium incorporates into cell membranes due to its biochemical behavior (Witschi and Aldridge, 1968); ii) the phytoplantkon bio-production in northern hemisphere (mussel food source) is higher in spring compared to the autumn season (Wildgust et al, 1998); iii) 7 Be (T 1/2 ¼ 53.4 days) enters the marine environment almost exclusively by atmospheric precipitation and/ or surface and groundwater discharges resulting in its considerably lower input to the marine environment during dry summer and early autumn seasons. Seasonal variations of 7 Be activities in mussels' soft tissue were also comparable to those measured for 210 Po (Ro zmari c et al, 2013) due to similar 7 Be and 210 Po bioaccumulation processes and their input to the marine environment.…”
Section: Resultsmentioning
confidence: 56%
“…Gallic acid as well as propolis extract might concomitantly reverse these marker enzymes by diminishing cellular damage (Fischer et al 2007), this was well supported by the morphological observations and showed the merit of combined therapy over monotherapy. Elevated hepatorenal ACPase indicated the injurious effects of beryllium on lysosomes (Witschi & Aldridge 1968), which are responsible for increased cellular autophagy, cell death and certain physiological and pathological conditions (Novikoff 1961). A reduction in the release of this enzyme after co-treatment with GA and propolis reflected conspicuous protection in the liver and kidney against beryllium toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is one of the principal target organs of the toxicological action of beryllium (Witschi & Aldridge 1968), and induction of AST, ALT and LDH reflected liver injury associated with necrosis, whereas g-GT pointed to hepatic cholestasis (Rodriguez-Garay 2003). Elevated levels of AST, ALT and LDH in the circulation indicated hepatic injury after beryllium exposure.…”
Section: Discussionmentioning
confidence: 99%
“…B. Lloyd, 1969 A number of metals are known to concentrate in lysosomes of liver and other cells (Witschi & Aldridge, 1968). Some of these metals are known to produce tumours at various sites and lysosomal involvement in carcinogenesis has been suggested (Allison, 1968).…”
Section: Latency Of Endogenous and Exogenousmentioning
confidence: 99%